Effect of Use of Spices on Shelf Life of Meat Rendang - Sri Murni, Dona; Syarif, Wirnelis (Universitas Negeri Padang, 2022)
This research was motivated by the different shelf life of beef rendang in West Sumatra. This study aims to determine the effect of using spices on the shelf life of beef rendang. The use of spices in the manufacture of beef rendang can be a natural preservative to extend the shelf life of beef rendang. This study used two treatments, namely beef rendang which used spices and beef rendang which did not use spices. The shelf life of beef rendang to be investigated is for 6 days with time intervals of day 1, day 3 and day 6. This type of research is quantitative and qualitative research using mixed methods (Mixed Method). This research was conducted 3 times in a row with 3 expert panelists. Quantitative data collection technique is an organoleptic test format whose data is processed by Independent Sample T-Test test and qualitative data is by observing and documenting the age of beef rendang. Based on the organoleptic test, it is known that the shelf life of beef rendang that uses spices and those that do not use spices is on day 1 to day 3 there is no change in beef rendang, on day 4 the meat already has a change in aroma and taste. on the 6th day of rendang already growing mushrooms on the surface of the rendang. If the beef rendang will be consumed for a long time, it is better to store the beef rendang in the freezer.